A case study of sexual harassment: an adolescent insecurity - Hana Suparti; Yonathan Salmon Ephraim Ngesti; David Ming (Jurnal Konseling dan Pendidikan)
Association is very important to explore and find identity for teenagers, but socialization is also vulnerable to mental threats in the form of insecurity that disturbs the future of teenagers. With this research, it is hoped that it can overcome or at least minimize the impact of youth insecurity due to association, so that the prospective youth of the nation's golden generation can avoid prolonged mental illness. Based on the background of this writing, the formulation of the research problem is obtained, namely: 1) How much influence does the association have on adolescent insecurity? 2) What are the patterns of causes and what are the forms of adolescent insecurity in the association?. This study was designed with the aim of explaining and answering the questions in the focus of the research above with the emphasis on: 1) Knowing the magnitude of the influence of association on the emergence of a sense of insecurity in adolescents. 2) State and explain the pattern of causes of insecurity in the association. With this research, researchers can find out in depth about the correlation between association and insecurity in adolescents.